2013
DOI: 10.1177/0892705712470263
|View full text |Cite
|
Sign up to set email alerts
|

Electrical application of polyamide reinforced with old tire rubber (ground tire rubber)

Abstract: Mass production of tires and their subsequent storage after use is a serious environmental problem that is tried to be solved in various ways. One of these ways is the mixture of these old used tires (ground tire rubber (GTR)) with various thermoplastic and thermostable polymers. These blends are made by modifying the pretreatment the GTR is subjected to, the degree of devulcanization, the mixing or pressing conditions, etc. Later the mixtures are analyzed structurally and mechanically, looking for possible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…To further analyze whether the yield strength was influenced by the corresponding variation in crystallinity (structural changes) or secondary interaction, the normalized yield strength ( σ yc / X c )/( σ ym / X m ) was plotted versus Φ f as shown in Figure 5(d). 26 The normalized yield strength values were >1 and the values increase continuously with Φ f ; at Φ f = 0.34, the parameter increases to 2.5 times that of PCL. Since the effect of crystallinity of PCL was eliminated, it may be emphasized that the increment in the yield strength is because of phase adhesion between JWF and PCL matrix which did not affect continuity of the matrix resulting a degree of increased stress transfer between JWF and PCL phase.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…To further analyze whether the yield strength was influenced by the corresponding variation in crystallinity (structural changes) or secondary interaction, the normalized yield strength ( σ yc / X c )/( σ ym / X m ) was plotted versus Φ f as shown in Figure 5(d). 26 The normalized yield strength values were >1 and the values increase continuously with Φ f ; at Φ f = 0.34, the parameter increases to 2.5 times that of PCL. Since the effect of crystallinity of PCL was eliminated, it may be emphasized that the increment in the yield strength is because of phase adhesion between JWF and PCL matrix which did not affect continuity of the matrix resulting a degree of increased stress transfer between JWF and PCL phase.…”
Section: Resultsmentioning
confidence: 87%
“…Stiffness of the system is not affected by phase interaction, however, tensile strength will vary promptly with phase interaction. 26 The mechanical restraint is an end result of differential thermal shrinkage of the polymer and the filler. When the polymer is melted, it expands to a higher extent as compared to JWF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of GTR negatively affects these properties, but suffers a certain drop in % elongation to percentages of 20% GTR (PA + 20% GTR: 23.30%, HDPE + 20% GTR: 20.01%) which already represents percentages less than 50% of the polymer matrix. Is observed that for elongation at break of the GTR compounds (for particle sizes <200 µm) [24,25], the optimum behavior is for EVA compounds, which go from 704% to 528%, 437%, and 351%, which means decreases of 29%, 43%, and 50% for GTR concentrations of 5%, 10%, and 20%, respectively. From 40% concentration, the values are always lower than 3.5 times those of pure EVA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Regardless of the type of polymeric thermoplastic used, GTR blends lack compatibility, mainly when the amount of GTR is higher than 20%. Therefore, it is often necessary to improve this lack of compatibility by performing surface treatments on GTR [24][25][26]. Considering this, we compared the results for insulators with low requirements in two programs, the Spanish Association for Standardization (UNE) and the International Electrotechnical Commission (IEC).…”
Section: Introductionmentioning
confidence: 99%